Pemanfaatan teknologi sudah dilakukan di banyak bidang kehidupan seperti sudah banyaknya aplikasi baik berbasis website ataupun android yang menjadi sahabat bagi semua lapisan masyarakat. Sebagian besar masyarakat hanya dapat menggunakan teknologi tersebu - Widayani, Hapsari; Burhanudin, Burhanudin (Jurnal Abdimas Musi Charitas, 2021)
This community service activity aims to help the financial service process at PKBM by using a well-designed and accurate design of an accounting of  receipt and disbursement.  The method used by author are begins with a process of interview, observation, and observation of cash receipt and disbursement and then collect the results that activities, and the last is introduce the result of the design to partners. Introducing result of design with giving the presentation to partners and direction so that the partners know about the flow. The analysis method use a descriptive analysis. This activity held at PKBM Patrakomala Bandung. The participants are employes, staff, and teachers. The product will be proceduced is system of cash receipt and disbursement that design attractive and well-structured. It’s expected that system can be used properly and developed further.